Síntese assistida por micro-ondas de novas bases de Schiff derivadas da Isatina com potencial atividade antineoplásica e anti-inflamatória - Silva, Girlyanderson Araújo da (2019)
Schiff’s Bases obtained from the derivatives of Isatin, have been calling researchers attention, in the field of medicinal chemistry, to their broad profile of pharmacological activities, such as anticancer, antimicrobial and antiviral. Recent studies have demonstrated a potential selectivity in the inhibition of COX 2, an enzyme responsible for inflammatory symptoms. In addition, they are present in important biological processes. This work was carried out with the aim of synthesize 12 Schiff’s bases derivate from isatin, being 6 unpublished, with potential biological activity. Initially, 11 intermediates derived from Isatin were synthesized using nitration, halogenation and alkylating reactions with yields varying from 51 to 93%. Subsequently, the Schiff’s bases were synthesized using microwave irradiation as a heating source. The methodology used was shown to be simple, fast and efficient for obtaining the products, showing good yields, income ranging from 57% to 98% in reaction times of 30 to 60 minutes. The products were characterized by infrared spectroscopy (IR) and MRI 1H and 13C.